1990
DOI: 10.1152/ajpendo.1990.258.1.e143
|View full text |Cite
|
Sign up to set email alerts
|

Direct evaluation of acidification by rat testis and epididymis: role of carbonic anhydrase

Abstract: The present experiments have employed microelectrode techniques (pH and PCO2) and microcalorimetry (total CO2 concentration) to define parameters of acidification in specific structures of the rat testis and epididymis during control conditions and after administration of the carbonic anhydrase inhibitor acetazolamide (20 or 50 mg/kg). Values for in situ pH during control conditions in seminiferous tubules (ST; 6.96 +/- 0.01), proximal caput (PCP; 6.62 +/- 0.01), middle caput (MCP; 6.59 +/- 0.01), middle corpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 24 publications
4
60
0
Order By: Relevance
“…Therefore, its presence in the epithelium of the epididymis, ductus deferens, and ampulla of the ductus deferens may also be linked to the acidification of the epididymal fluid via bicarbonate reabsorption. This hypothesis is compatible with an earlier report suggesting that bicarbonate reabsorption rather than H' secretion is the mechanism of epididymal fluid acidification in the rat (Caflisch and DuBose, 1990). The lack of CA I1 in the epithelia of the human epididymis and the proximal ductus deferens also supports the concept that bicarbonate reabsorption by CA IV plays a pivotal role in the acidification of the epididymal fluid.…”
Section: Sds-pagesupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, its presence in the epithelium of the epididymis, ductus deferens, and ampulla of the ductus deferens may also be linked to the acidification of the epididymal fluid via bicarbonate reabsorption. This hypothesis is compatible with an earlier report suggesting that bicarbonate reabsorption rather than H' secretion is the mechanism of epididymal fluid acidification in the rat (Caflisch and DuBose, 1990). The lack of CA I1 in the epithelia of the human epididymis and the proximal ductus deferens also supports the concept that bicarbonate reabsorption by CA IV plays a pivotal role in the acidification of the epididymal fluid.…”
Section: Sds-pagesupporting
confidence: 91%
“…The physiological role of cytoplasmic CA I1 in the distal parts of the reproductive tract is probably linked to equipping of the seminal plasma with bicarbonate required for maintaining sperm motility after ejaculation. However, the spermatozoa are subjected to an acidic environment during passage through the epididymis, which probably accounts for their quiescence there (Caflisch and DuBose, 1990;Carr et al, 1985). It has been suggested that carbonic anhydrases play a central role in the acidification of epididymal fluid (Au and Wong, 1980;Cohen et al, 1976), but it has remained uncertain which one of these isoenzymes is involved.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that these transporters and pump could not have contributed to the Isc, and by inference HCOצ secretion, on account of the fact that the Na¤-H¤ exchanger, H¤-ATPase, and Na¤-HCOצ cotransporter have been implicated in HCOצ secretion in other epithelia (see Gleeson, 1992;Raeder, 1992). Thirdly, contrary to the earlier work of Tuck et al (1970), a more recent micropuncture study by Caflisch & DuBose (1990) showed that the rat seminiferous tubular fluid contains a very low concentration of HCOצ. These results led these authors to argue that active HCOצ secretion is not an important factor in the formation of the seminiferous tubular fluid.…”
Section: Discussionmentioning
confidence: 91%
“…159 Many of these characteristics mirror those of the tumourigenic niche. 149 Whereas such a niche promotes tumours in neoplastic cells in other organs, epididymal cells normally survive in this environment.…”
Section: Rarity Of Epididymal Cancer Ch Yeung Et Al 472mentioning
confidence: 99%